Integrated current-sensing circuit with offset-current cancellation for dc-dc boost converters using 0.13um CMOS technology / Intan Shazana Shamsul Sahar - Shamsul Sahar, Intan Shazana (2015)
The project proposed a configuration of CMOS current sensing circuit with offset-current cancellation for boost converters. This design will contrast the power and operational sensing speed with the traditional proposed current-sensing circuit. By eliminating the offset-current, it will improve the current sensing performance. It can be accomplish by applying current mirror as opposed of utilizing operational amplifier as a voltage follower in conventional design which serves to subside power consumption due to reducing the number of transistor. Moreover, this proposed design also can cancel off the offset-current in the traditional current sensing circuit, thus the improvement of sensing-accuracy will accomplished. The proposed design will be designed using 0.13um technology and simulation will be carried out in Mentor graphics. The dc-dc boost converter will be set with operating frequency of 500kHz and designed with the supply voltage of 2V.